2019
DOI: 10.22146/jcoemph.38410
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi status gizi, somatotipe, asupan makan dan cairan pada atlet atletik remaja di Indonesia

Abstract: Athletes’ nutrition status, somatotype, and adequate dietary intake are strongly related to their sport performance. Examining those markers in adolescent age is essential in order to develop the optimum physical characteristics for the future. This study was conducted to identify the nutrition status based on anthropometry value, somatotype, food and fluid intake of youth athletic athletes in Indonesia. Descriptive quantitative design was used in this study. Subjects participated in the study were 25 youth at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 7 publications
1
9
0
6
Order By: Relevance
“…Anthropometric measurements in athletes are aimed to determine the nutritional status based on measurements of weight, height, BMI, and other anthropometric aspects 12 . These also needed to determine the physical conditions related to athletic performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropometric measurements in athletes are aimed to determine the nutritional status based on measurements of weight, height, BMI, and other anthropometric aspects 12 . These also needed to determine the physical conditions related to athletic performance.…”
Section: Resultsmentioning
confidence: 99%
“…Athletes' nutritional status is one of the important factors affecting their performance, especially for adolescent athletes. Nutritional status assessment in adolescent athletes is essential to observe the optimal growth and development of athletes 12 . Nutritional status determination in adolescence can be measured based on height-for-age (HAZ) and body mass index-for-age (BMI for age).…”
Section: Resultsmentioning
confidence: 99%
“…Berbagai studi pada atlet di Indonesia juga mengungkapkan terjadinya asupan zat gizi yang tidak seimbang, seperti yang ditemukan pada atlet pelajar di berbagai pusat pembinaan atlet (Penggalih et al, 2016;Penggalih et al, 2019). Kajian yang dilakukan oleh (Tahir et al, 2019) di PPLP Provinsi Sulawesi Selatan menyatakan bahwa kecukupan energi tergolong sangat kurang, karbohidrat dan protein tergolong kurang, serta lemak tergolong normal.…”
Section: Pendahuluanunclassified
“…Globally, various studies described that athletes are vulnerable to nutrition deficiencies, whether in junior athletes (Kim et al, 2019;Michael et al, 2019) or elite athletes (Jenner et al, 2018;Ong and Brownlee, 2017). Studies in Indonesian youth athletes showed that inadequate nutrition intake was frequently found in sport schools and athlete training centers (Penggalih et al, 2016(Penggalih et al, , 2017(Penggalih et al, , 2018. The flawed nutrition intervention strategy, lack of education about nutrition's importance for athletic performance, and the absence of nutritionist role in the sport management team were some of the reasons for the nutritional problems in athletes (Jenner et al, 2018).…”
Section: Introductionmentioning
confidence: 99%